AsiaInfo : technology markets in China (B) - Sanderson, Jihong W.; Geng, Jiao (London : SAGE Publications Ltd, 2017)
In 1993 in Texas, a newly formed company, Business Development International (BDI), had no assets, no professional managers, no business plan, and no product. Yet the founders were firm in their resolve to bring information and communication to largely uneducated and isolated China. By 2003, their new venture AsiaInfo was the dominant brand in Chinese Internet Infrastructure and a major force in telecommunications software, and it had grown along with the explosive growth of Internet use in China. As great as the challenge of growing the company to match the rapidly growing industry in China was, other challenges proved even greater.
Originally published in Sanderson, J. W., & Geng, J. (2003). AsiaInfo: Technology markets in China (B). The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; AsiaInfo; Entrepreneurship -- China; Business planning -- China